The impact of Brexit on regional productivity in the UK - Bernard Fingleton; Ben Gardiner; Ron Martin; Luca Barbieri (ZFW - Advances in Economic Geography, 2023)
In June 2016, the UK voted to leave the European Union (Brexit). It took until January 2021 before a trade deal was finally agreed and the UK's departure was com- pleted. There have been a number of studies have sought to estimate the impact of Brexit on the UK's regions, mostly using approximations or inferred measures of regional trade . Our focus in this paper is somewhat different, namely on the impact of Brexit regional productivity cross the UK, a key element of the UK Government's concern over geographical inequalities in economic performance. Using a state-of-the-art spatial model, a novel aspect of which is allowing for spatial and temporal spillovers, we are able to estimate the impact of various drivers of regional variations in labour productivity, notably capital per skilled worker, human capital, and goods exports to the EU. We apply the model estimates to simulate the regional impact of post-Brexit reductions in goods exports, finding in particular that in the long run, productivity in the London regions is likely to be less adversely affected than in other regions.
Keywords: 330; regional productivity; Kaldorian theory; exports; impact of Brexit